2013
DOI: 10.1103/physrevlett.110.135701
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Freezing of Argon in Completely Filled Mesopores

Abstract: We have studied the phase transition of argon in completely filled mesopores. Our effective medium analysis of ultrasonic measurements clearly indicates a continuous phase transition of argon in completely filled pores over a broad temperature range of about 45 K. With decreasing temperature, the amount of frozen argon increases and below about 30 K all adsorbed argon (including the first few layers near the pore wall) is frozen with a shear modulus about equal to the bulk shear modulus. It is remarkable, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 44 publications
2
52
2
Order By: Relevance
“…The phase transition quantization exemplifies in a remarkable manner how confinement can alter the physics of liquid crystals [14,18,25,31,32,[52][53][54][55][56][57][58][59][60][61][62][63] and allows us to determine the otherwise hard to access bend elastic constant [64]. More generally, it highlights how curved geometries can alter self-assembly and crystallization [14,23,24,65,66] and how versatile soft matter can adapt to extreme spatial constraints with new architectural principles dynamics, as has been similarly discussed for simple molecular [38,[67][68][69] and polymeric systems [70][71][72][73][74][75]. Finally, we envision that the spontaneous, temperature-tunable nanoscale ring formation demonstrated here along with the one-dimensional charge carrier pathways and mechanical stability of the membranes may provide a versatile playground for the study of electronic and magnetic confinement effects [76] or even of the fluid-wall-interaction-induced deformations of nanopores [77].…”
Section: (B)mentioning
confidence: 99%
“…The phase transition quantization exemplifies in a remarkable manner how confinement can alter the physics of liquid crystals [14,18,25,31,32,[52][53][54][55][56][57][58][59][60][61][62][63] and allows us to determine the otherwise hard to access bend elastic constant [64]. More generally, it highlights how curved geometries can alter self-assembly and crystallization [14,23,24,65,66] and how versatile soft matter can adapt to extreme spatial constraints with new architectural principles dynamics, as has been similarly discussed for simple molecular [38,[67][68][69] and polymeric systems [70][71][72][73][74][75]. Finally, we envision that the spontaneous, temperature-tunable nanoscale ring formation demonstrated here along with the one-dimensional charge carrier pathways and mechanical stability of the membranes may provide a versatile playground for the study of electronic and magnetic confinement effects [76] or even of the fluid-wall-interaction-induced deformations of nanopores [77].…”
Section: (B)mentioning
confidence: 99%
“…[1][2][3][4][5] Freezing of liquids confined at the nanoscale is also relevant to applications involving lubrication, nanotribology, and fabrication of nanomaterials. 6,7 Some experimental and theoretical works on simple liquids have proposed that the in-pore freezing point T f is shifted to lower (higher) temperature with respect to the bulk freezing temperature showing that the freezing point for cyclohexane between parallel mica surfaces in a surface force apparatus is not elevated but decreased with respect to the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Beamish and co-workers used it to study the properties of liquid helium [11][12][13] and also proposed ultrasonic experiments for probing the surface area of nanoporous materials [14]. Later ultrasonic experiments became widely used for studying phase transitions in confinement, both liquid-vapor [15][16][17][18] and solid-liquid [19][20][21][22][23][24][25][26][27][28]. Among these works, it is worth pointing out the paper of Page et al [16], which first showed that when the pores are completely filled with a liquid-like capillary condensate, the modulus of the fluid (n-hexane) was not constant, * Corresponding author, e-mail: gennady.y.gor@gmail.com but a monotonic function of the gas pressure p (lower pressure corresponds to lower modulus).…”
Section: Introductionmentioning
confidence: 99%